Analisis Kinerja Simpang Bersinyal Dan Penanganan Dampak Kemacetan Pada Jalan Raya Jenggala – Jalan Raya Pahlawan Kecamatan Gedangan Dengan Metode PKJI 2023: Analysis Of Signalized Intersection Performance And Handling Of Congestion Impacts On Jenggala Road – Pahlawan Road, Gedangan Sub-District Using The PKJI Method 2023 - Efristka Anggraeny; Nugroho Utomo; Dzulfiqar Alfiansyah (Media Ilmiah Teknik Sipil, 2026)
The Jenggala Highway – Pahlawan Highway intersection is located in an industrial warehouse area and adjacent to a railway crossing. This condition causes this intersection to have a high level of traffic activity and causes congestion. From these problems, the performance of this intersection has a saturation degree of 1.07 in the afternoon and an intersection delay of 54.87 seconds/SMP. Therefore, this intersection requires treatment to make the intersection performance more efficient. The treatment carried out was replacing the signal phase setting from initially 2 phases to 3 signal phases and East approaches are not allowed to turn left. So the saturation degree value after treatment was 0.75 in the afternoon and a decrease in intersection delay of 37.90. This saturation degree value has met the performance requirements for signalized intersections, which is less than 0.85 according to the handbook Indonesian Road Capacity (PKJI) 2023.